2021
DOI: 10.3390/ijerph18083933
|View full text |Cite
|
Sign up to set email alerts
|

Does the End Justify the Means? The Role of Organizational Communication among Work-from-Home Employees during the COVID-19 Pandemic

Abstract: During the first months of 2020, the world, and Italy at an early stage, went through the Covid-19 emergency that had a great impact on individual and collective health, but also on working processes. The mandatory remote working and the constant use of technology for employees raised different implications related to technostress and psycho-physical disorders. This study aimed to detect, in such a period of crisis and changes, the role of organizational communication considering the mediating role of both tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 128 publications
0
48
0
2
Order By: Relevance
“…Molino et al [32] demonstrated the risk factors for behavioral stress among Italian workers using different technologies during COVID-19. Other researchers have considered the influence of organizational communication using technologies on psycho-physical disorders during the COVID-19 pandemic [33]. Nevertheless, organizational researchers have not yet thoroughly examined how acceptance of new technologies has impacted employees' work-related well-being during COVID-19 remote working.…”
Section: Introductionmentioning
confidence: 99%
“…Molino et al [32] demonstrated the risk factors for behavioral stress among Italian workers using different technologies during COVID-19. Other researchers have considered the influence of organizational communication using technologies on psycho-physical disorders during the COVID-19 pandemic [33]. Nevertheless, organizational researchers have not yet thoroughly examined how acceptance of new technologies has impacted employees' work-related well-being during COVID-19 remote working.…”
Section: Introductionmentioning
confidence: 99%
“…The research did not show that employees from home office work with greater intensity than in the office, as mentioned by Gruber (2019) or Zito et al (2021). Respectively, none of the respondents mentioned this in the interview.…”
Section: Sharing Messages (41%)mentioning
confidence: 62%
“…This is further complicated by the increasing use of remote working devices and modalities, which can undoubtedly have a positive impact on speeding up processes and improving performance, even if they pose a potential challenge to workers’ wellbeing. For example, previous research has shown a relationship between remote work and technostress [ 33 , 34 ], work-life balance [ 35 ] and burnout [ 36 ], but also a positive relationship with performance [ 37 ].…”
Section: The Challenges Of the “Sandwich” Middle-management’s Leadership In Managing Work-life Interfacementioning
confidence: 99%